(3GdeYjGQ GdeYQH hGdLGeY GdeZQH Yf aJGhi YdeGA EaQjbjI hGdCfOdS hGdeZQHs - (3CHh GdYHGS CMeO Hf jMji Hf eMeO Hf YHO GdhGMO Hf Ydj GdhfTQjSj,J (B914 (3g` s ((3LYaQ Hf YHO Gddg GdMfai s)
(3ChdgG (B:s
(3fhGRd GdfcGM SFd CHh YHO Gddg MK QShd Gddg Ydi fcGM GdCHcGQ aCLGH s
(3BNQgG (B:s
(3hGdLhGH Yf GdeSCdI GdKGfjI YTQI Cf eG CYWi GdCH Yf CHfg UOGbkG Ef cGf Ydi hLg GdMed ai CUd YbOg GdfcGM adHbjg GdhQKI GdbjGe Ydjg HYO ehJ GdhGdO , abO fLR GdLRA GdKGdK s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI fajSI heUMMIs
(3cJHJ GdahGJM HGdCShO GdSejc s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3Gdabg GdESdGejs